Birth Defects in the Sons and Daughters of Women who were Exposed in utero to Diethylstilbestrol (DES) - Titus-Ernstoff, Linda (2009)
BACKGROUND: Prenatal exposure to diethylstilbestrol (DES) is associated with adverse health outcomes, including anatomic anomalies of the reproductive tract in women and of the genitourinary tract in men. The mouse model, which replicates many DES-related effects seen in humans, suggests that prenatal DES exposure causes alterations that may affect the next generation of offspring. METHODS: Women participating in a large multi-center study of prenatal DES exposure were asked to report birth defects occurring among 4,029 sons and 3,808 daughters (i.e., the third generation). A subcohort of 793 third generation daughters were also queried for birth defects. We used logistic regression models to generate odds ratios and 95% confidence intervals for the association between prenatal DES exposure in the mother and birth defects in the offspring. RESULTS: Based on the mothers’ reports, overall birth defects were elevated in the sons (OR = 1.53; 95% CI = 1.04, 2.23) and in the daughters (OR = 2.35; 95% CI = 1.44, 3.82). Most estimates of association were imprecise, but daughters appeared to have an excess of heart conditions (OR = 4.56; 95% CI = 1.27, 16.34. CONCLUSIONS: . Our data suggest a possible association between the mother’s prenatal DES exposure and birth defects in their offspring, particularly in daughters. We cannot, however, rule-out the possible influence of reporting bias. In particular, the exposed daughters’ elevated risk of cardiac defects may be due to the underreporting of these conditions by unexposed mothers.